Carotenoid Profile, Antioxidant Capacity, and Chromoplasts of Pink Guava (Psidium guajava L. Cv. ‘Criolla’) during Fruit Ripening - Rojas Garbanzo, Carolina (2017)
Pigments of pericarp and pulp of pink guava (Psidium guajava L. cv. ‘Criolla’) were investigated to elucidate the profile and the accumulation of main carotenoids during four stages of fruit ripening by using HPLC-DAD and APCI-MS/MS analysis. Seventeen carotenoids were identified, and changes in their profile during fruit ripening were observed. The carotenoids all-trans-β-carotene, 15-cis-lycopene, and all-trans-lycopene were present in all ripening stages, but all-trans-lycopene was found to be predominant (from 63% to 92% of total carotenoids) and responsible for the high lipophilic antioxidant capacity determined by spectrophotometric assays. By using light and transmission electron microscopy, the development of chromoplasts in pericarp and pulp was demonstrated. The accumulation of all-trans-lycopene and all-trans-β-carotene coincided with the development of large crystals; the chromoplasts of pink guava belong, therefore, to the crystalline type.